Biophysical and computational approaches to unravel the molecular interaction mechanism of bromodeoxyuridine, a proliferative marker with human serum albumin - Roslan, Amira Adlin; Kandandapani, Salanee; Ridzwan, Nor Farrah Wahidah; Mohamad, Saharuddin; Tayyab, Saad (Springer Verlag, 2019)
Abstract: The interaction of a nucleoside analogue bromodeoxyuridine (BrdU) with human serum albumin (HSA) was studied to investigate the binding phenomenon and analyse the protein conformation upon BrdU binding. Multiple spectroscopic techniques, viz. intrinsic and 3-D fluorescence, UV–Vis absorption, and circular dichroism (CD) spectroscopy along with molecular docking were used. Decrease in the Stern–Volmer constant (Ksv) as well as the association constant (Ka) with increase in temperature suggested BrdU–HSA complex formation. Intermediate binding affinity between BrdU and HSA was evident from the Ka values (2.49–3.97 × 104 mol–1 dm3), while BrdU–HSA complex formation was driven by hydrophobic and van der Waals interactions along with hydrogen bonds, as revealed by thermodynamic data (ΔS = + 28.48 J mol−1 K−1; ΔH = − 17.16 kJ mol−1). Minor changes occur in both secondary and tertiary structures as well as in the fluorophores’ microenvironment of HSA, as recognized from the CD spectral results in the far-UV and the near-UV regions and 3-D fluorescence spectra, respectively. Use of site markers (warfarin and indomethacin for site I; diazepam for site II) as well as docking results suggested BrdU binding to both site I (more preferred) and site II, located in subdomains IIA and IIIA, respectively, of HSA. Graphic abstract: [Figure not available: see fulltext.]. © 2019, Springer-Verlag GmbH Austria, part of Springer Nature.